THE CONCEPT TERM “LUCKY-PER” IN HENRIK PONTOPPIDAN’S NOVEL: CRITICAL ANALYSIS THROUGH DAINISH MEDIA AND LITERATURE - HAMMER, K. (Філологічні науки, 2020)
The article compares the features of realism in the artistic prose of the modern Danish writer Henrik Pontoppidan and the famous classics of the era of Romanticism of the time of H. C. Andersen. The purpose of the article was ti carry out the media analysis of realistic features in the novel ʺLucky-Perʺ, in particular, to analyze the genre and style dominants, the influence of Andersen’s reminiscences on the main motives of the novel. The novel of both H. Pontoppidan and H.C. Andersen is written within the frame of the dual tradition, since in the investigated novel the signs of two epochs as romanticism and realism are combined. The auther cast the light on the novel ‘Lykke-Per’ as a monumental and canonical work in Danish literature which since the publication has been read by new generations repeatedly. The novel takes place in the late 1800s and gives a weighty picture of Denmark in the country and in the city, and tells about the convulsions in society. First, it is a psychological development novel, in which Per, through his love relations with women, but also in the encounter with men from different status layers, develops and forms as a human being. “Lucky Per” is a novel you will think of long after reading it because of the many layers. The successful screen version of Bille August will increase the desire to read or reread the magnificent work. The author singles out the common feature of both novels which is a dominant in the social hemisphere of both epochs of the novels. Thus, the author presents existential reasons for motives of exhaustion, abandonment, loneliness. The novel ʺThe Lucky Pearlʺ is a deeply tragic book that talks about the hopes of youth and bitter disappointments, about the illusions that have been lost, the main theme is the fate of the younger generation of the Danish intelligentsia at the turning point in the countryʹs development.